PENGARUH BEBAN KERJA DAN FASILITAS KERJA TERHADAP EFEKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PADA PT WIEDA SEJAHTERA - Muhammad Rayhan; Azwar *; Anwar Mustofa (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2022)
This study aims to determine and analyze the effect of partially and simultaneously between workload and work facilities on the work effectiveness of production employees at PT Wieda Sejahtera. This study includes causal associative research with a quantitative approach and a population of 30 workers with a sample calculation using a saturated sampling technique. The number of samples used in this study were 30 respondents. Testing the instrument using validity and reliability tests. While the data analysis method used multiple linear regression analysis, the coefficient of determination R2 test, T test, and F test. Data processing in this study was carried out using SPSS 22 software for windows. The regression equation model Y= 50,997 - 0,464 (X1) + 0,542 (X2) + is feasible to use. Based on the partial correlation results, the workload variable (X1) has an effect on work effectiveness (Y) of 10.96 percent, while the work failure variable (X2) has an effect on work effectiveness (Y) of 12.89 percent. Based on the results of the analysis of the coefficient of determination (R2) of 29.3 percent work effectiveness is influenced by workload and work facilities while the remaining 70.7 percent is influenced by other variables not discussed in this study such as motivation, work stress, leadership style and so on.